MENINGKATKAN SRADHA DAN BHAKTI MELALUI AJARAN PANCA SRADHA - I Gede Sugiarka (Yayasan Pendidikan Literasi Borneo, 2025)
The teachings of Panca Sradha are the main foundation in Hindu teachings which include five basic beliefs, namely belief in the existence of God (Brahman), Atman (soul), Karma Phala (law of cause and effect), Punarbhava (rebirth), and Moksa (spiritual liberation). This study aims to analyze efforts to improve Sradha (faith) and Bhakti (devotion) of Hindus through the implementation of the teachings of Panca Sradha in everyday life. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation of religious figures, traditional leaders, and Hindus in the research area. The results of the study indicate that understanding and practicing the teachings of Panca Sradha can strengthen the Sradha and Bhakti of the people, especially through increasing awareness of the spiritual relationship between humans, nature, and God. In addition, the implementation of these teachings in the form of religious rituals, meditation, and social activities can instill moral and ethical values that support harmony in life. This study also found that religious education based on Panca Sradha in the family and community environment plays an important role in building the character of Hindus based on faith and devotion. Thus, this study recommends strengthening Hindu religious education that emphasizes the implementation of Panca Sradha and increasing the role of traditional institutions and religious figures in guiding people to practice these teachings. This is expected to encourage Hindus to further improve Sradha and Bhakti in religious, social, and cultural life